Seroprevalence of and Risk Factors for Toxoplasma gondii among Pregnant Women in Abyek Township of Qazvin Province , Iran (2013) - Tabatabaie, Fatemeh; Mafi, Morteza; Golestani, Mohsen; Shahmohammad, Narges; Mafi, Hadi; Maleki, Fatemeh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Toxoplasmosis is an important disease which is caused by the coccidian parasite Toxoplasma gondii. The aim of this study was to determine seroprevalence of and risk factors for T. gondii among pregnant women in Abyek township of Qazvin province by enzyme-linked immunosorbent assay method. Methods: Blood samples were taken from 200 pregnant women referred to the health centers of Abyek township. Immunoglobulin M (IgM)and IgG titers and effects of some factors on incidence of the disease were evaluated. The collected data were statistically analyzed with SPSS 17 using Chisquare test. Results: Anti toxoplasma IgM and IgG were positive in 2% and 29% respectively. Seropositive subjects were more frequently seen in women with age >30 years compared to younger women. No significant relationship was found between the seroprevalence of T. gondii infection and level of education, residence area, history of abortion and gestational age. Conclusion: It was indicative of having a latent infection due to the previous exposure to toxoplasma parasite in this region. Keywords: Toxoplasma gondii, Prevalence, Pregnant women, Enzyme-linked immunosorbent assay, Immunoglobulin M.